Fundus autofluorescence and SD‐OCT in progressive cone dystrohy - Hassairi, A.; Falfoul, Y.; Turki, A.; Maamouri, R.; El Matri, K.; Chebil, A.; El Matri, L. (Acta ophthalmologica (Oxford, England), 2016)
Purpose To describe fundus autofluorescence (FAF) and Spectral domain optic coherence tomography (SD‐OCT) findings in progressive cone dystrophy (PCD) and evaluate the benefits of these methods for diagnosis. Methods All patients with the diagnosis of PCD based on color sense, visual field and electrophysiological tests were included. They underwent full ophthalmic examination with best‐corrected Snellen visual acuity (BCVA), fundus photography, SD‐OCT and FAF. Results Sixteen eyes of 8 patients were included. Mean age was 36.5 years and 19 years at the beginning of signs. Mean BCVA was 0.18 (range 0.05–0.4). On biomicroscopy, we found changes in the retinal pigment epithelium ranging from barely detectable changes (6 eyes) up to the typical bull's eye appearance (8 eyes). We found central macular atrophy in 2 eyes. OCT showed statistically significant reduction in the thickness and structural changes in the macular retina, predominating at the perifoveolar zone in 8 cases. Atrophy was evident especially in the outer nuclear layer and the ellipsoid zone. Visual acuity was mainly dependent on the degree to which the continuity of the ellipsoid was maintained in subfoveolar. FAF was normal in 2 eyes, showed heterogeneous hyper‐FAF in 4 eyes, hypo‐FAF in 2 eyes, small area of mild hypo‐FAF in the perifoveal region surrounded by a ring of hyper‐FAF in 8 eyes. The junction between normal and abnormal outer retina on OCT corresponded to the hyper‐autofluorescent ring. Conclusions OCT and FAF specifies the quantitative and qualitative changes in the macula and may contribute significantly to the diagnosis of the progressive cone dystrophy, particularly in the early stages of the disease which is difficult to diagnose.